Propuesta técnica de una planta de tratamiento y transformación de gas natural licuado para la zona sur occidente del país (2021)
In the development of this project we will obtain the result of a regasification Plant in the southwest of the country; which has the ability to sweeten, dehydrate and liquefy gas. This is because the gas is dissipating and there is not the capacity to treat it. First, a description is made of each of the treatments to be carried out on the gas, then its usual operation with the processes and equipment used and finally the results of the chromatography are used to characterize the components.